PERAN MEDIA OLAHRAGA SEBAGAI SARANA DAKWAH DALAM PERKEMBANGAN DAKWAH ISLAM - Tatang Hidayat; Muh Fadhlan Anshorullah; Istianah Istianah (INSTITUT AGAMA ISLAM NEGERI PONTIANAK, 2025)
The purpose of this research is to analyze the role of sports media as a means of da'wah in the development of Islamic da'wah. This research uses a descriptive qualitative approach in the form of library research. A literature review of literature sources that are sources of information and data is used to collect data. Based on the results of the research, sports media is very important for the growth of Islamic da'wah, especially in modern times when people are increasingly interested in sports such as soccer, badminton, volleyball, table tennis, sepak takraw, basketball, boxing and UFC. Sports are not only for keeping fit, but can also be used as a medium for preaching. Athletes play an important role in spreading the teachings of Islam. The attitudes shown by Muslim athletes such as covering aurat, praying before starting the match, prostrating gratitude when winning, not shaking hands with non-mahrams, drinking while sitting, and preaching Islam at every event when they are invited or on their respective social media accounts can inspire their fans. Not only do athletes inspire through their achievements, they can also inspire and have a positive impact on the people around them through their religion.